The relationship between service quality and customer satisfaction at Chancellery of Universiti Malaysia Terengganu / Norain Abd Wahid - Abd Wahid, Norain (2014)
This study attempts to examine the relation ship between service quality and customer satisfaction at Chancellery of Universiti Malaysia Terengganu. The study was conducted using a se t of questionnaire to 285 employees of Universiti Malaysia Terengganu and a convenience sampling is employed . Th e survey instruments included a demographic survey , service quality and customer satisfaction . The study was used SPSS for windows 19 .0 statistical software to organize and analyze all the data collected. The collected data was analyzed using descriptive analysis and correlation analysis. There result of the study showed that there is a significant relat10nship between service quality and customer satisfaction at Chancellery of Universiti Malaysia Terengganu. Meanwhile the result of this study contributed to existing theory by confirming the relationship between service quality, customer satisfaction and SERVQUAL dimensions. Besides that, this study may be important because it ma y provide valuable information for top management in order to comprehend significant relationship regarding the service quality and customer satisfaction level in relation its organization .